Introduction to artificial intelligence and expert systems - Patterson, Dan W. (New Delhi : Prentice Hall, 1990)
This text provides comprehensive treatment of all important topics in artificial intelligence and expert systems - presented from a knowledge based systems approach. The text covers the knowledge and knowledge representation methods in both breadth and detail, with many examples, covers the latest results in all key areas of AI, including knowledge representation, pattern matching, natural language processing, computer vision, memory organization, pattern recognition, expert systems, neural networks, AI tools and machine learning. throughout. The book provides chapter introductions and chapter summaries.